Metodologia de planejamento e controle da produção para obras de engenharia natural - Sousa, Rita dos Santos (2019)
Soil Bioengineering consists of a group of techniques that combine live construction materials with inert materials which can be applied as constructive solutions to structural problems of geotechnical and hydraulic stabilization, control surface erosion processes, and simultaneously designs ecosystems in dynamic equilibrium. In Soil Bioengineering works are not used performance assessment procedures standardized, through methodologies. The production planning and control are informally conducted in an empirically and subjectively way. With the increasing worldwide use of these techniques, the level of customer requirement, the limited availability of financial resources for works execution and competition between companies comes up the need for the development of a standardized system for management of Soil Bioengineering works, particularly at the level of the production planning and control (PCP). Taking these issues into consideration, the aim of this work is to develop a methodology of PCP for Soil Bioengineering works, considering the concepts and principles of lean construction. A methodology was developed with the integration of three hierarchical levels: strategic, tactical and operational and was specified a system of key performance indicators adapted to the specificities of Soil Bioengineering. Afterwards, the methodology was validated through the practical application to a work performed in Brazil. The developed methodology promoted the application of the lean construction principles. Had focus on the effectiveness of the work execution process, according to the term and the programmed sequence, increasing the reliability of production, greater visibility in relation to the expectation of work conclusion, as well as, the identification of causes of deviations that interfered with work execution and the increased efficiency in the use of resources. The proposed PCP model can be considered as an integration tool between the company different management functions, especially regarding the mitigation of the losses in the production process associated with the costs, deadlines or quality, providing consistency, transparency and rationality in the collection and dissemination of information within the organization. The design, implementation and use of key indicators system for performance measurement in Soil Bioengineering works is innovative at an international level. The proposed PCP and key performance indicators promoted the understanding of the results and deviation causes, supporting the decision-making process and the implementation of corrective measures that aim continuous improvement of the process and of the organization as a whole. The proposed model may change as learning process, consolidation of concepts and continuous improvement occur in the company. In this case new methods, procedures, techniques or key performance indicators can be established.